The effects of size, shape and surface functionality on in vivo biodistribution and toxicity: A multiparametric biochemical study of gold nanomaterials - Özçiçek, İlyas; Altuncu, N.; Çakıcı, Çağrı; Aydeğer, Asel (Wiley, 2021)
Gold nanomaterials have a widespread use due to their superior physical and chemical properties. Gold nanoparticles and nanorods are very popular and stable metallic nanomaterials which can be synthesized easily in various sizes and surface chemistry and their surfaces can be functionalized by desired polymers. They have a wide range of uses in medicine, electronics, pharmacy, chemistry, biology and biomedical fields. Gold nanomaterials are often preferred for cell and tissue imaging,
Keywords: Toxicity; Gold Nanomaterials; Surface Functionality